Ubiquitous Listening : Affect, Attention, and Distributed Subjectivity - Kassabian, Anahid (Book collections on Project MUSE., 2013)
How does the constant presence of music in modern life-on iPods, in shops and elevators, on television-affect the way we listen? With so much of this sound, whether imposed or chosen, only partially present to us, is the act of listening degraded by such passive listening? In Ubiquitous Listening, Anahid Kassabian investigates the many sounds that surround us and argues that this ubiquity has led to different kinds of listening. Kassabian argues for a new examination of the music we do not normally hear (and by implication, that we do), one that examines the way it is used as a marketin.